IT‐supported innovation management in the automotive supplier industry to drive idea generation and leverage innovation. Issue 4 (17th November 2011) - Neumann, Martin; Riel, Andreas; Brissaud, Daniel; Biró, Miklós; Messnarz, Richard; Palacios, Ricardo Colomo
SUMMARY Innovative product development is highly dependent on new product ideas and product information. This especially applies to companies that obtain their competitive advantages by technological lead like the automotive supplier industry. Innovation management in these industries has to focus on an efficient idea generation, implementation and capitalisation, and on technology tracking. This paper gives an insight into the industry‐sector‐specific characteristics of innovation management within the automotive supplier industry, and outlines a basic scheme of an innovation management system that aims at improving the existing innovation management at the automotive supplier Kolbenschmidt Pierburg AG. Copyright © 2011 John Wiley & Sons, Ltd.